Business Law in an Aerospace Perspective in Indonesia - Maharani, Charity Ega (Dinasti International Journal of Management Science, 2024)
This scientific article aims to analyze in depth the problems and challenges faced by the aerospace industry in Indonesia from the perspective of business law. This research will use a qualitative approach to deeply understand the legal issues affecting the aerospace industry. This approach allows researchers to explore the experiences, views, and interpretations of various stakeholders. This research method is designed to explore and analyze the legal aspects of business in the aerospace industry in Indonesia. The main focus is on understanding how regulations and laws affect operations and compliance in the industry and how they impact airlines, aircraft operators, and passengers. The results of this study from the researcher's perspective provide an insight and reference where the importance of adaptive business models and flexible regulations in the aviation industry is important. Technological innovations such as electric aircraft and drones offer the potential to improve efficiency and sustainability, but they require the right regulatory support. On the other hand, customer satisfaction remains key to business success, especially through responsiveness to complaints and adjustment to changing expectations due to global events such as COVID-19. Collaboration between all stakeholders is needed to create an environment that supports growth and innovation in the industry.